Arsenic toxicity manifesting as profuse watery diarrhea during induction therapy for acute promyelocytic leukemia. Issue 5 (15th May 2021) - Ott, Ashley; Venkataraman, Vinayak; Badran, Yousef R.; Goldman, Rose; Spasic, Smiljana; Vyas, Darshali A.; Amrein, Philip; McAfee, Steven; Brunner, Andrew; Fathi, Amir T.; Narayan, Rupa
Abstract: Arsenic trioxide (ATO) is generally well tolerated for treatment of APL. We present a patient with severe watery diarrhea and pancreatitis thought to be due to ATO toxicity in the setting of obesity and acute kidney injury. Future studies evaluating ATO levels in patients experiencing toxicities may help guide dose modifications. Abstract : Arsenic trioxide (ATO) is generally well tolerated for treatment of APL. We present a patient with severe watery diarrhea and pancreatitis thought to be due to ATO toxicity in the setting of obesity and acute kidney injury. Future studies evaluating ATO levels in patients experiencing toxicities may help guide dose modifications.